Reassessing the Star of Bethlehem in Matthew 2: Astronomy, Theology, and the Ethiopian Angelic Tradition - Belay Sitotaw Goshu (Lakhomi Journal Scientific Journal of Culture, 2026)
The Star of Bethlehem in Matthew 2:1–12 has long resisted definitive explanation, with astronomical hypotheses (planetary conjunctions, comets, novae) and theological readings often proceeding in isolation. The Ethiopian Orthodox Tewahedo tradition, which identifies the star as the Archangel Michael, remains virtually unknown in mainstream scholarship. This review reassesses the star by integrating three lenses: natural astronomical candidates, theological functions within Matthew’s narrative, and the Ethiopian angelic interpretation. An interdisciplinary review of astronomical literature (retrospective celestial mechanics, ancient Chinese records), patristic exegesis (Origen, Chrysostom), and Ethiopian primary sources (The Book of the Mysteries of the Heavens and the Earth, 15th c.), supplemented by liturgical and architectural analysis. No single astronomical candidate fully accounts for the star’s narrative behaviors (cessation, reappearance, “standing over” a house). Patristic writers, especially Chrysostom, interpreted the star as an angelic power. The Ethiopian tradition uniquely names the star as Michael, embeds this identification in the Genna Christmas procession (candles, three circuits of the church), and reflects it in the eastern orientation of the “Bethlehem” prothesis room. Conclusion: The star is best understood as a “providentially timed convergence” natural astronomical event (e.g., the 5 BCE comets) used by God as the vehicle for angelic guidance and theological revelation. The Ethiopian voice resolves narrative difficulties and enriches the interdisciplinary conversation. Future research should systematically survey Ge‘ez manuscripts (e.g., Te’amrä Iyasus, homiliaries) and compare Ethiopian angelology with Coptic and Syriac traditions.